(untitled) (Revista de Educação Pública, 2012)
Importa discutir, nos limites deste texto, quais as influências que as tensões de nível teórico-prático da modernidade e da pós-modernidade são mais claramente identificadas em âmbito científico. Discute-se o legado da modernidade e os elementos que revelam as novas tendências teóricas, chamadas de pósmodernas, que abandonam categorias de análise dos fenômenos da realidade que situam as lutas de classes e o processo histórico, optando por uma centralidade para a compreensão crítica do real. Em que bases são consolidadas as políticas públicas brasileiras e qual a leitura se pode fazer no âmbito dessas tensões? Theoretical tensions between modernity and Post-Modernity: effects in the brazilian public politics Abstract This essay aims to show what influences in the practical and theoretical levels of tensions of Modernity and Post-Modernity are more clearly identified on scientific scope. Discusses the legacy of Modernity and the elements that reveal the new theoretical tendencies, called Post-modernity, that abandon analysis category of reality phenomena that establishes the class struggles and the historical process with centrality for the critical comprehension of reality. In which basis are the Brazilian public politics consolidated and what can we understand about the scope of these tensions? Key-words: Modernity. Post-modernity. Public politics.